Application of Nanocomposite Energy Storage Materials in Green Building Design - Ying Xu (International Journal of Analytical Chemistry)
In order to solve the problem of the application of composite phase change heat storage materials in building energy conservation, the author proposes the application of nanocomposite energy storage materials in green building design. Modified carbon nanotubes were prepared by mixed acid oxidation and ball milling, and composited with stearic acid to prepare phase change heat storage materials. Modified carbon nanotubes were prepared by mixed acid oxidation and ball milling and composited with stearic acid to prepare phase change heat storage materials. Experimental results show that acidified carbon nanotubes have a hindering effect on the thermal diffusion of stearic acid molecular segments so that the thermal conductivity of carbon nanotubes added with a mass fraction of 1% is only 1.3 times higher than that of pure stearic acid. Conclusion. Nanocomposite energy storage materials have excellent application prospects in green building design.